The liquidity premium in CDS transaction prices: Do frictions matter? - Monika Gehde-Trapp; Yalin Gündüz; Julia Nasev (University of Cologne, Centre for Financial Research (CFR), 2015)
Based on individual CDS transactions cleared by the Depository Trust & Clearing Corporation, we show that illiquidity strongly affects credit default swap premiums. We identify the following effects: First, transaction direction affects prices, as buy (sell) orders lead to premium increases (decreases). Second, larger transactions have a higher price impact. This finding stands in stark contrast to corporate bond markets. Third, traders charge higher premiums as a price for liquidity provision, not as compensation for asymmetric information. Fourth, buyside investors pay significantly higher prices than dealers for demanding liquidity. Last, inventory risk seems to matter little in explaining liquidity premiums.
Keywords: G12; G14; 330; CDS; illiquidity; temporary price impact; market power; immediacy; DTCC